PENGARUH BLENDED LEARNING TERHADAP HASIL BELAJAR EKONOMI PESERTA DIDIK KELAS XI IPS MAN 1 PONTIANAK - Fitri Dianti; Mashudi Mashudi; Husni Syahrudin (Universitas Tanjungpura, 2022)
Research aims to understands blended learning on the learning outcomes of students in class XI IPS MAN 1 Pontianak. The form of survey research with a quantitative approach using ex post facto methods. The population in this study werw students of class XI IPS MAN 1 Pontianak, and a sample of 107 students was obtained using the probability sampling method. The date collection method uses questionnaires that are distributed to student, then analyzed with simple regression analysis techniques. Research results: (1) the percentage of blended learning is 75,08% (hight category). (2) the economic learning outcomes of students are indicated by the end of semester test scores with an average of 86,13. (3) there is an influence of blended learning on learning outcomes. The magnitude of the influence of blended learning on learning outcomes was 0,17 with a percentage of the remaining 31,7% influenced by other factors that were not discussed in the study. The sig value of 0.000 < 0,5 then Ha accepted and H0 rejected. it was concluded that “blended learning influences on economic learning outcomes of class XI IPS MAN 1 Pontianak”